2016
DOI: 10.26655/mjltm.2016.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Gaining proficiency in speaking skill has always been a great point of concern for potential EFL communicators. This need is now more concrete than any time before. In face-to-face communication contexts, plenty of such factors as anxiety, shyness and not being enough proficient are demotivating and inhibit the individuals to communicate with native-speakers. Along with the emergence of the virtual world, the cyber space, where you can stay anonymous and yet express yourself in the most comprehensive way, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Advocating its implementation, language teachers take responsibility for creating opportunities to help develop students' autonomy. Baghi et al (2016) suggested using journal writing as a practical device to boost autonomous learning among students. This helps facilitate teaching and learning writing (Marefat, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Advocating its implementation, language teachers take responsibility for creating opportunities to help develop students' autonomy. Baghi et al (2016) suggested using journal writing as a practical device to boost autonomous learning among students. This helps facilitate teaching and learning writing (Marefat, 2002).…”
Section: Introductionmentioning
confidence: 99%